LEKER SI KOAL berbasis STEM Education untuk Mengukur Kemampuan Penalaran Matematis - Fiqhiya Hasnal Mala; Tri Novita Irawati; Sholahudin Al Ayubi (Universitas Islam Jember, 2021)
This study aims to develop LEKER SI KOAL (Lembar Kerja Siswa Konteks Aljabar) based on STEM Education as a learning media for measuring mathematical reasoning abilities. The research was conducted at MTs Ma'arif Ambulu involving 32 class VII students. Data was collected through questionnaires, tests, observations, interviews, and documentation, and the model of development research that was used is ADDIE which consisted of five stages: analysis, design, development, implementation, and evaluation. The results of the development of LEKER SI KOAL show that this learning media is included in the